A Review on Hybrid Closed Loop Insulin Delivery System (Advances in Applied Biological Research, 2025)
Type 1 diabetes mellitus (T1DM) is a habitual autoimmune condition taking lifelong  insulin remedy. Conventional approaches like multiple quotidian injections or  continuous subcutaneous insulin infusion are limited by hypoglycaemia trouble,  glycaemic variability, and patientburden. Automated insulin delivery (AID)  systems, particularly crossbred unrestricted- circle (HCL) systems, integrate  continuous glucose monitoring, insulin pumps, and control algorithms to optimize  insulin delivery. HCL systems automate rudimentary insulin and correction  boluses, taking manual mess boluses, and haves hown significant benefits,  including increased time- in- range (TIR), lower HbA1c, reduced hypoglycaemia,  and enhanced quality of life. These benefits are seen across different populations,  including children, grown- ups, and pregnant women. Despite these advancements,  limitations remain, analogous as mess gelcap dependence, delayed post- mess  glucose control, sensor delicacy issues, cost, and specialized malfunctions. fully  unrestricted- circle systems are being developed to count manual input and  further mimic physiological insulin regulation. With ongoing advances,HCL  systems represent a significant step toward a fully independent artificial pancreas,  offering bettered glycaemic control, safety, and quality of life for individualities  with T1DM. These systems have the eventuality to revise diabetes operation and  meliorate patientissues.
Keywords: Type 1 diabetes mellitus; Automated insulin delivery; Hybrid Closed-Loop System; Continuous Glucose Monitoring; Artificial pancreas